Knowledge, Perception, and Experience of Dentists About Teledentistry - Walter Raucci-Neto; Mariele de Souza Pereira; Nathália Mancioppi Cerqueira; Victoria Gabriela Louzada; Larissa Moreira Spinola de Castro Raucci; Graziela Bianchi Leoni (Elsevier, 2022)
Objectives: This study aimed to evaluate the level of knowledge, perception, and experience of teledentistry amongst Brazilian dentists with the ongoing COVID-19 pandemic. Methods: Between June and July 2020, an online questionnaire was used to collect information on the demographic and professional profiles of dentists and their levels of knowledge, perception, and attitudes towards teledentistry. Descriptive statistics were reported as percentages, and Chi-squared test was used to compare responses amongst general practitioners, specialists, and those with varying levels of professional experience. Results: This study included 575 dentists, the majority of whom were from the southeast region of Brazil (73.4%) and had a specialist degree (70.4%). Approximately 42.4% of the study sample had graduated more than 10 years ago, 39.3% between 2 and 10 years ago, and 18.3% up to 2 years ago. In general, the majority of dentists exhibited only a superficial awareness of the resolution that regulates teledentistry in Brazil. A greater number of specialists were aware of the resolution (P = .007) and felt confident performing teledentistry (P = .000) compared to general practitioners, whilst those with more experience (graduated more than 10 years ago) exhibited greater knowledge (P = .012) and preparation (P = .000). More than 60% of the dentists, regardless of dental specialty and clinical experience, had no knowledge of providing prescriptions via teledentistry. The majority of general practitioners (89.5%) and specialists (81.4%) had no previous experience using teledentistry. Conclusions: The findings of this study suggest that Brazilian dentists are inadequately prepared for the implementation of teledentistry.